Surotul Mar ati al-Ijabiyah fi Al-Amsal al-Arabiyati Wa al-Amsali al-Swahiliyah (Dirosah Muqoronah) - Faisal Masoud Muhindo (IJAS: Indonesian Journal of Arabic Studies, 2020)
This study aimed to reveal the image of women in Arabic and Swahili Proverbs, and to identify the issues and meanings addressed by the owners of the environment in which the proverbs were said and broadcasted, in addition to highlighting the sweetness felt in the proverbs of humor and anagrams, which enhances literary pleasure. The research methodology used for this study was the comparative approach whereby an image of women was presented through Arabic and Swahili proverbs, and the researcher also used the descriptive analytical approach to highlight the contents of proverbs and their significance to reveal the image of women that reflects their status in society, and this enabled the researcher in comparing the image of omen between Arabic and Swahili proverbs. The results of the research indicated that there are proverbs in Arabic and Swahili languages that glorifies women and raises their status which are few when compared to  other proverbs that detract their status and reduce their value, we sometimes find that the two extremes coexist in one example. تهدف هذه الدراسة إلى الكشف عن صورة المرأة بين الأمثال العربية والأمثال السواحلية والوقوف على القضايا والمعاني التي يتناولها أصحاب البيئة التي قيلت وذاعت فيها الأمثال، فضلاً عن إبراز العذوبة المحسوسة في الأمثال من فكاهة وجناس مما يعزز المتعة الأدبية. وكان منهج البحث المسخدم لهذه الدراسة هو المنهج المقارن، إذ به تمت تقديم صورة عن المرأة من خلال الأمثال العربية والأمثال السواحلية، كما استعان الباحث بالمنهج الوصفي التحليلي لتسليط الضوء على مضامين الأمثال ودلالتها للكشف عن صورة المرأة التي تعكس وضعها في المجتمع، وهذا مكن الباحث من قيام بمقارنة صورة المرأة بين الأمثال العربية والأمثال السواحلية. وكانت نتائج البحث تشير إلى وجود أمثال في اللغة العربية واللغة السواحلية تمجد المرأة، وترفع من شأنها إلا أنها قليلة، إذا ما قورنت بالأمثال التي تحط من مكانتها وتقلل من قيمتها، حتى إننا نجد أحياناً تعايش النقيضين في مثل واحد.